KEGIATAN KRING RESERSE DALAM MENCEGAH TP CURANMOR RODA DUA - Franto akcheryan Matondang (Advances in Police Science Research Journal, 2019)
ABSTRACT Crime theft of two-wheeled motorized vehicles is the highest crime conventional in the last three years in the city of Bandung. Various prevention efforts have been carried out, one of which is the implementation of a police investigation by the Bandung Criminal Investigation Unit. In this study, researchers solved the problem by using management theory, routine activity theory, and competency theory along with the detective ring concept, the concept of preventing and the concept of motorized vehicles. problems that occur. Data collection was carried out such as interviews, observations and document studies combined with triangulation of data in order to find out the effectiveness of the data. From the results of research and discussion by the author, several findings were obtained as follows: SOP of detective ring that was made in 2017. 2) Inequality in the number of officers with responsibility in the area of ​​the ring and there are still many officers who lack competence. 3) Budget which is not available from DIPA and Sarpras is still lacking. 4) The method used is not appropriate. Based on the results of the study the authors advise as follows: 1) It is recommended that the Criminal Investigation Unit conducts a Kring detective SOP update based on the stages stipulated in the Police Operational Management. 2) Submission of personnel to attend vocational education and detective training. 3) Submission of DIPA for the implementation of the investigation and procurement of infrastructure facilities that are lacking or damaged. 4) There is coordination with other units such as Sabhara, Binmas and Bhabinkamtibmas in conducting preventiveactions. Keywords: Criminal Investigation Ring; Sat Criminal Investigation; Curanmor R2; Bandung Polrestabes